Jerusalem artichoke: A sustainable biomass feedstock for biorefinery. (February 2016) - Long, Xiao-Hua; Shao, Hong-Bo; Liu, Ling; Liu, Li-Ping; Liu, Zhao-Pu
Abstract: The biggest challenge for the production of bulk commodities such as biofuels and bio-based chemicals through biorefinery is to secure low-cost biomass feedstocks on a large scale. Current sugar- and starch-based feedstocks are not sustainable due to their main usage as food or food ingredients for humans. Although lignocellulosic biomass, particularly agricultural residues, is abundantly available, its conversion and utilization are still not economically competitive. One solution is to develop specific energy crops that can grow well on marginal land without competing for arable land with grain production. Jerusalem artichoke ( Helianthus tuberosus L.) is tolerant to environmental stresses such as drought and salinity as well as plant diseases, and thus is an alternative energy crop. The biomass of Jerusalem artichoke comes mainly from its tubers containing inulin as a major component, which can be hydrolyzed into fermentable sugars without an energy-intensive pretreatment. In this article, genetic resources, cultivar selection and planting of Jerusalem artichoke are reviewed. Compared to other herbaceous energy crops, particularly switchgrass and Miscanthus that have been intensively studied in the United States and Europe, not only can Jerusalem artichoke be used as feedstock for producing biofuels and bio-based chemicals, but also value-added products to make the biorefinery process more economically competitive.